Pengaruh Profitabilitas, Leverage, dan Good Corporate Governance terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Pemoderasi - Sanusi, Anwar; Alteza, Muniya; Hidayah, Nuri Lesmono (Forum Kerjasama Pendidikan Tinggi, 2025)
This research examines the determinants of firm value: profitability, leverage, and corporate governance. In addition, the research examines dividend policy as a moderating factor in the determinants of firm value. The research was conducted on food and beverage companies listed on the Indonesia Stock Exchange during 2018-2022. The approach used is quantitative with an associative causality method. Sample collection was done using a purposive sampling method, resulting in 19 companies. The data obtained is unbalanced panel data with a total of 91 observations. Data analysis uses moderated regression analysis techniques. The research results prove that partially profitability, leverage, and corporate governance each have a positive and significant influence on firm value. Dividend policy moderates the influence of profitability, leverage, and corporate governance on firm value. Simultaneous testing shows that there is a goodness of fit of the model to explain the firm value.